Determinants of Fourth Industrial Revolution Technology Adoption in Zimbabwean State Universities: A TechnologyOrganization-Environment Framework Analysis - Dlamini, Banele; Schutte, Danie P. (International Journal of Economics and Financial Issues, 2025)
This study investigates the determinants of Fourth Industrial Revolution (4IR) technology utilisation in Zimbabwean state universities using the Technology–Organisation–Environment (TOE) framework. A quantitative research design was adopted, using structured questionnaires to collect data from 163 respondents across seven public universities. Data analysis involved descriptive statistics, reliability testing, exploratory factor analysis, and multiple regression. Findings reveal that all three TOE dimensions significantly predict 4IR utilisation (p < 0.001). Technological readiness, especially perceived ease of use, tool availability, and usefulness was the strongest driver. Organisational factors, including leadership commitment and digital culture, were also critical, while environmental enablers such as supportive policy and stakeholder collaboration showed a weaker but significant effect. Demographic results indicated high educational attainment and awareness of 4IR, yet persistent disparities in access, particularly among students. The study underscores the need for integrated strategies that combine infrastructure investment, institutional capacity building, and enabling policy frameworks. It contributes to TOE literature in resource-constrained higher education systems and offers practical insights for advancing digital transformation in the Global South.